2013
DOI: 10.1002/mame.201200337
|View full text |Cite
|
Sign up to set email alerts
|

Direct Electrospinning of Cellulose–Chitosan Composite Nanofiber

Abstract: The direct electrospinning of a non‐derivatized cellulose (Cs)–chitosan (Ch) composite nanofiber is described for the first time. Either of two cellulose preparations from different sources, i.e., cotton (CsC) or bamboo (CsB), is fabricated into composite electrospun non‐woven fabrics (ESNWs) with Ch using the trifluoroacetic acid–acetic acid mixed solvent. The total concentration of Cs + Ch in the mixed solvent is fixed at 4.0 wt.‐% with various Cs/Ch weight ratios of 8:2, 5:5 (Figure shows CsB/Ch‐ESNW), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…10 Less than 1% of WL was observed for the salt-free Cs/Ch-ESNW, which indicated the complete removal of TFA after treatment with 0.1 N NaOH/EtOH. Elemental analysis of the salt-free ESNW revealed that more than 99% of the chitosan was retained after immersion in water, which also supported the complete removal of the TFA.…”
Section: Electrospinning and Insolubilization Of Cs/ch-esnwmentioning
confidence: 96%
See 2 more Smart Citations
“…10 Less than 1% of WL was observed for the salt-free Cs/Ch-ESNW, which indicated the complete removal of TFA after treatment with 0.1 N NaOH/EtOH. Elemental analysis of the salt-free ESNW revealed that more than 99% of the chitosan was retained after immersion in water, which also supported the complete removal of the TFA.…”
Section: Electrospinning and Insolubilization Of Cs/ch-esnwmentioning
confidence: 96%
“…10 Briefly, the pre-spun solutions of Cs and Ch in TFA/AcOH were separately prepared. The Cs and Ch solutions were mixed at the weight ratio of Cs : Ch ¼ 4 : 6, and the total concentration of the blend solution was fixed at 4 wt%.…”
Section: Preparation Of Cellulose-chitosan Esnwsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were unable to fabricate blends with a higher cellulose content. Furthermore, acetic acid (AcOH) can be incorporated as a cosolvent with TFA to help reduce solution viscosity and enhance solution spinnability and has been used for the electrospinning of cellulose-chitosan composite fibres [15] and as an aqueous solvent for electrospinning cellulose acetate [16] and chitosan nanofibres [17]. It has also been used to control the viscosity of solutions in TFA when casting neat cellulose films [18] and blend films of cellulose and chitosan [19], [20].…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning can fabricate planar and three-dimensional structures by applying polymeric, metallic, ceramic, and organic materials [1][2][3][4]. In laboratories, electrospinning has been widely used to produce composite nanofibers [5], filtering films [6], solar cells [7], microsensors [8], and tissue scaffolds [9].…”
Section: Introductionmentioning
confidence: 99%